Filaggrin mutations increase allergic airway disease in childhood and adolescence through interactions with eczema and aeroallergen sensitization. Issue 2 (30th January 2018) - Chan, Adrian; Terry, William; Zhang, Hongmei; Karmaus, Wilfried; Ewart, Susan; Holloway, John W.; Roberts, Graham; Kurukulaaratchy, Ramesh; Arshad, Syed Hasan
Summary: Background: Filaggrin loss‐of‐function ( FLG ‐LOF) mutations are an established genetic cause of eczema. These mutations have subsequently been reported to increase the risk of aeroallergen sensitization and allergic airway disease. However, it is unclear whether FLG variants require both eczema and aeroallergen sensitization to influence airway disease development long‐term outcomes. Objective: To examine the effects of FLG ‐LOF mutations on allergic airway disease outcomes, with eczema and aeroallergen sensitization as intermediate variables, using the Isle of Wight birth cohort. Methods: Study participants were evaluated at ages 1, 2, 4, 10 and 18 years to ascertain the development of allergic diseases (eczema, asthma and allergic rhinitis) and aeroallergen sensitization (determined by skin prick tests). FLG ‐LOF mutations were genotyped in 1150 subjects. To understand the complex associations between FLG mutations, intermediate variables (eczema and aeroallergen sensitization) and airway disease, path analysis was performed. Results: There were significant total effects of FLG ‐LOF mutations on both asthma and allergic rhinitis at all ages as well as on aeroallergen sensitization up till 10 years old. In the filaggrin‐asthma analysis, a direct effect of FLG ‐LOF mutations was observed on early childhood eczema (age 1 and 2 years) (relative risk (RR) 2.01, 95% CI: 1.74‐2.31, P  < .001), and all significant indirect pathways on asthma outcomes passed through eczema at these ages. In contrast, for the filaggrin‐rhinitis model, FLG ‐LOF mutations exerted significant direct effects on early eczema as well as rhinitis at 10 years (RR 1.99; 95% CI: 1.72‐2.29, P  = .002). Conclusion: FLG ‐LOF mutations are a significant risk factor for later childhood asthma and rhinitis. However, the pathway to asthma is only through early childhood eczema while a direct effect was observed for childhood rhinitis.